Biogas Production from Palm Oil Mill Effluent (POME) by Optimum Level of Inputs - MAMUNUR, RASHID (Universiti Malaysia Sarawak (UNIMAS), 2019)
The aim of this study is to optimize biogas production from POME by using anaerobic reactor with various Organic Loading Rate, Carbon-Nitrogen ratio and Hydraulic Retention Time. For conducting this research, a two-stage fermentation anaerobic reactor has been used at OLR rate 1, 2.6, 5, 9 and 11 g/L.d ; at C/N ratio 14.54, 20, 28, 36, 41.454. and at HRT 2.295, 4, 6.5, 9, 10.70 days. The anaerobic reactor is operated at mesophilic temperature (350C) for 30 days. The finding of this research demonstrates the optimum input values are OLR is 5 (g/d. L), C/N is 28, HRT is 6.5 days and output of Biogas is 3.8 L/d from POME. This finding will bring benefits to palm oil industries in achieving economic and environmental sustainability. This research concludes that in-depth research into this matter is important to implement this technology in the palm oil industry.